Spore Production by Biocontrol Agent Trichoderma Harzianum in Submerged Fermentation: Effect of Agitation and Aeration - Said, Syahiddin Dahlan (Jurnal Rekayasa Kimia & Lingkungan, 2007)
Effects of agitation and aeration on spore production and spore viability by biocontrol agent UPM 29 were investigated. The optimum fermentation at different agitation speeds, ranging from 300 rpm to 700 rpm show that there is an optimum agitation speed gives the highest spore production. The spore production increased with increasing agitation speed from 300 rpm to 500 rpm. At the higher agitation speed the spore production dropped. The highest spore concentration (9.2x107 spores/ml) was produced in culture grown on media with agitation speed of 500 rpm. The rate of aeration effected spore production and spore productivity in the range 1.5 to 2.0 vvm, and increased the spore production from 4.7x107 to 6.0x107 spores/ml (28% increase) and 4.7x108 to 8.1 x108 spores /l/h respectively. The spore viability was not affected significantly by aeration rate or agitation speed.Keywords: agitation, biocontrol agent, biofungicide, spore viability, Trichoderma harzianum